Alopecia areata/Loose anagen syndrome. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2022)
Alopecia areata and loose anagen syndrome are different diseases. However, sometimes the latter can present with a patch of very thin hair (Fig. 2) and simulate alopecia areata.